Effects of increasing credit limit in digital microlending: A study of airtime lending in East Africa. Issue 3 (6th September 2021) - Shema, Alain
Abstract: The recent decade has witnessed a significant increase in digital micro‐lending in Africa, boosted by the surge in popularity of mobile phones and, especially, mobile money. Starting with airtime and cash lending through mobile money, numerous other products are now offered, including prepaid electricity vouchers. However, these innovative loan products are often hampered by a lack of credit history from customers. Thus, lenders resort to issuing small loan amounts that are expanded as customers make timely repayments. Research from the credit card industry shows that increasing credit limits can lead to increased indebtedness and spending. Working with an airtime lender, this experimental study finds that people with increased credit limits behave similarly to credit cardholders, by increasing their borrowing. However, this increased borrowing negatively affects their repayment rate and long‐term usage of communication services. Additionally, customers' characteristics, such as their borrowing experience, influence their responses to increases in credit limits. Based on the results of this experimental study, we present key recommendations for digital micro‐lenders to minimize the potential negative impacts of increasing credit limits. We also discuss the use of randomized experiments as a research method in ICTD studies.